Dorylaimid and Tylenchid Nematodes Associated with Banana Plantations in Paschim Medinipur District, West Bengal, India - Gantait, Viswa Venkat; Chatterjee, Amalendu; Bhattacharya, Tanmay (Journal of the Bombay Natural History Society (JBNHS), 2013)
We recorded 46 species of soil and plant parasitic nematodes belonging to the Orders Dorylaimida and Tylenchida from rhizospheric soil and roots of banana plantations in Paschim Medinipur district, West Bengal from March 2004 to February 2006. Dorylaimida is represented by 29 species under 21 genera of 8 families; 8 species are new to science. Tylenchida is represented by 17 species belonging to 11 genera under 7 families; 4 species are new to science. Among the 46 species, 15 species (13 dorylaimids and 2 tylenchids) were reported for the first time from West Bengal and 5 species (3 dorylaimids and 2 tylenchids) for the first time from India. Sixteen species (12 dorylaimids and 4 tylenchids) were recorded for the first time from the rhizosphere of banana.